Comprehensive genomic profiling: Does timing matter? - Thapa, Bicky; Ahmed, Gulrayz; Szabo, Aniko; Kamgar, Mandana; Kilari, Deepak; Mehdi, Maahum; Menon, Smitha; Daniel, Sherin; Thompson, Jonathan; Thomas, James; George, Ben (Frontiers in Oncology, 2023)
Purpose: There is variability in the utilization of Comprehensive Genomic Profiling (CGP) in most metastatic solid tumors (MST). We evaluated the CGP utilization patterns and their impact on outcomes at an academic tertiary center. Patients and Methods: Institutional database was reviewed for CGP data in adult patients with MST between 01/2012 – 04/2020. Patients were categorized based on the interval between CGP and metastatic diagnosis; 3 tertiles of distribution (T1-earliest to the diagnosis, T3-furthest), and pre-mets (CGP performed prior to diagnosis of metastasis). Overall survival (OS) was estimated from the time of metastatic diagnosis with left truncation at the time of CGP. The Cox regression model was used to estimate the impact of timing of CGP on survival. Results: Among 1,358 patients, 710 were female, 1,109 Caucasian, 186 Afro-Americans, and 36 Hispanic. The common histologies were lung cancer (254; 19%), colorectal cancer (203; 15%), gynecologic cancers (121; 8.9%), and pancreatic cancer (106; 7.8%). The time interval between diagnosis of metastatic disease and CGP was not statistically significantly different based on sex, race, and ethnicity after adjusting for histologic diagnoses with 2 exceptions - Hispanics with lung cancer had delayed CGP compared to non-Hispanics (p =0.019), and females with pancreas cancer had delayed CGP compared to males (p =0.025). Lung cancer, gastro-esophageal cancer, and gynecologic malignancies had better survival if they had CGP performed during the first tertile after metastatic diagnosis. Conclusion: CGP utilization across cancer types was equitable irrespective of sex, race, and ethnicity. Early CGP after metastatic diagnosis may have a greater impact on OS in cancer types with more actionable targets.